Umbilical Cord Blood Culture is Reliable for the Diagnosis and Management of Infants at Risk for Early-Onset Sepsis - Murray, Emily J.; Mattioli, Maria; Rauscher, Devon; Pryzchowicz, Elizabeth; Winstanley, Moira; Carola, David; Aghai, Zubair H. (American Journal of Perinatology, 2025)
This study aims to compare the diagnostic utility of umbilical cord blood culture (UCBC) versus neonatal blood culture (NBC) in the evaluation and management of early-onset neonatal sepsis (EONS) in late preterm and term infants and determine the contamination rate of UCBC.A retrospective analysis was conducted on late preterm and term neonates born between December 2020 and January 2025, who underwent EONS evaluation with UCBCs and NBCs. The study assessed detection rates of true-positive cultures, contamination rates (false positives), and incidence of culture-negative sepsis.A total of 336 infants had UCBCs performed, with 223 undergoing concomitant NBCs. Positive culture rates were similar: Four UCBCs (1.2%) and three NBCs (1.3%) were positive. UCBC had two contaminants (0.6%) while NBC had one (0.45%). One infant had both cultures positive for Escherichia coli. No infants required prolonged antibiotics for culture-negative sepsis.The contamination rate of UCBC was extremely low in the cohort of infants at high risk for EONS. Our protocol and collection technique may serve as a model for others aiming to reduce contamination rates. While NBC can be positive despite a negative UCBC, and vice versa, obtaining both UCBC and NBC can improve the sensitivity of EONS diagnosis and help minimize prolonged antibiotic use in cases of culture-negative sepsis. UCBC demonstrated a low contamination rate and comparable diagnostic yield to NBC. UCBC may be considered a reliable alternative or adjunct to NBC in the evaluation and management of EONS.
Keywords: sepsis; neonates; blood culture; cord blood